2020
DOI: 10.1002/advs.202000726
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Active Cardiac Patches as an Untethered, Non‐Blood Contacting Ventricular Assist Device

Abstract: Patients suffering from heart failure often require circulatory support using ventricular assist devices (VADs). However, most existing VADs provide nonpulsatile flow, involve direct contact between the blood flow and the device's lumen and moving components, and require a driveline to connect to an external power source. These design features often lead to complications such as gastrointestinal bleeding, device thrombosis, and driveline infections. Here, a concept of magnetically active cardiac patches (MACPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Some devices aimed at restraining the heart geometry passively while adapting their properties at the different cardiac cycle phases [237]. More frequently, instead, the assistance was also active: in a recent work [238], authors reported a magnetically actuated AD mounted onto a 3D-printed patch able to improve the ejection fraction of 37% in the left ventricle and 63% in the right one. Another actuating principle was used in [239], where the authors presented a silicone-based material embedding electrothermally-responsive fibers (Dragon Skin 10 with silver-coated nylon yarn, Shieldex Trading, USA).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Some devices aimed at restraining the heart geometry passively while adapting their properties at the different cardiac cycle phases [237]. More frequently, instead, the assistance was also active: in a recent work [238], authors reported a magnetically actuated AD mounted onto a 3D-printed patch able to improve the ejection fraction of 37% in the left ventricle and 63% in the right one. Another actuating principle was used in [239], where the authors presented a silicone-based material embedding electrothermally-responsive fibers (Dragon Skin 10 with silver-coated nylon yarn, Shieldex Trading, USA).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…[51,261,262] 3) The applications in giant machinery, such as, aerospace, including smart load-bearing and anti-impact structures, [1,27,46,181,263] morphing airfoils, [264] acoustic stealth cloaks, [48,[225][226][227] elastic mechanical cloaks, [48] reconfigurable antenna, [24,180,265,266] terahertz metadevices, [267] electromagnetic stealth system. [268][269][270] 4) The applications in biomedicine include electronic skin, [258,[271][272][273][274][275] tissue engineering, [192,194,[276][277][278][279][280] vascular stents, [54,136,[281][282][283] drug delivery carriers. [136,210,284,285] From the above discussion, the rich functions and application value of AMMs have brought great convenience to human production and life.…”
Section: Practical Applications Of Active Mechanical Metamaterialsmentioning
confidence: 99%
“…[ 51 , 261 , 262 ] 3) The applications in giant machinery, such as, aerospace, including smart load‐bearing and anti‐impact structures, [ 1 , 27 , 46 , 181 , 263 ] morphing airfoils, [ 264 ] acoustic stealth cloaks, [ 48 , 225 , 226 , 227 ] elastic mechanical cloaks, [ 48 ] reconfigurable antenna, [ 24 , 180 , 265 , 266 ] terahertz metadevices, [ 267 ] electromagnetic stealth system. [ 268 , 269 , 270 ] 4) The applications in biomedicine include electronic skin, [ 258 , 271 , 272 , 273 , 274 , 275 ] tissue engineering, [ 192 , 194 , 276 , 277 , 278 , 279 , 280 ] vascular stents, [ 54 , 136 , 281 , 282 , 283 ] drug delivery carriers. [ 136 , 210 , 284 ,…”
Section: Functions and Practical Applications Of Active Mechanical Metamaterialsmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 ] Progresses in manufacturing are further expanding the design landscape through the possibility to code magnetization profiles in soft magnetoresponsive composites. [ 5 , 6 , 7 , 8 ] Both current coils systems [ 9 , 10 ] and permanent magnets were adopted as field sources. Compared to coils, which permit higher‐frequency modulation and the possibility to switch off the field, permanent magnets can generate stronger fields and gradients, and their application is not restricted by wiring and cooling requirements, thus fostering their attractiveness for heat‐sensitive biomedical procedures.…”
Section: Introductionmentioning
confidence: 99%